Evaluation of fit feasibility of stock total joint replacement in temporomandibular joint ankylosis patients. Issue 7 (September 2021) - Alagarsamy, Ragavi; Roychoudhury, Ajoy; Bhutia, Ongkila; Lal, Babu; Yadav, Rahul; Bhalla, Ashu Seith
Abstract: Long standing adult temporomandibular joint ankylosis (TMJA) results in smaller ramal height, and warped and undulated ramus. Despite the efforts made to standardise the sizes available in stock joint (Zimmer Biomet®), the system causes fit challenges in TMJA patients. The aim of the study was to evaluate the virtual feasibility of stock prostheses in TMJA patients. The data included amount of bone contouring for fossa placement, available ramal length, length discrepancy if placed straight, angulation of mandibular component required to adapt to the bone, and mediolateral fit discrepancy. CT data of 50 TMJA patients (71 joints; unilateral, n = 29; bilateral, n = 21; male, n = 33; female, n = 17) with mean age of 24.26 ± 8.88 years were included. 53 joints required more than 3 mm lateral bone reduction for fossa placement. The ramal length were categorised into ranges 35–40 mm (n = 15), 41–45 mm (n = 14), 46–50 mm (n = 28) and >50 mm (n = 14). Correlation between the age of occurrence of ankylosis and ramal length using the Pearson correlation coefficient revealed a positive correlation (r = 0.38, p = 0.001). Length discrepancy, angulation of mandibular component, and mediolateral fit discrepancy decreases as the ramal length increases. Only 14 joints had appropriate fit of stock prostheses while the remaining 57 joints warranted compromised placement. Even the smallest available stock mandibular component (45 mm) had a compromised fit in terms of length and adaptability on the lateral aspect of ramus. The study concludes that a short ramus is mostly limiting factor in using stock prosthesis in TMJA patients. There is a need for still smaller size stock prostheses.